2009
DOI: 10.1097/wnn.0b013e3181b278f9
|View full text |Cite
|
Sign up to set email alerts
|

Depression Impairs Executive Functioning in Parkinson Disease Patients With Low Educational Level

Abstract: Patients with PD present with cognitive impairment even when nondemented. Depression may exacerbate executive dysfunction, especially in subjects with lower educational level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0
6

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 37 publications
1
25
0
6
Order By: Relevance
“…The increased tendency of older patients and those with less education, longer disease duration and more severe motor disabilities to exhibit poor frontal lobe function is consistent with the result of another study of 82 PD patients, which found that younger patients and those with higher education performed better on the FAB test and that the severity of the disease was correlated with FAB performance [24] . Our study also found that patients with longer disease duration and more severe motor disabilities exhibited more severe frontal behavioral changes.…”
Section: Discussionsupporting
confidence: 87%
“…The increased tendency of older patients and those with less education, longer disease duration and more severe motor disabilities to exhibit poor frontal lobe function is consistent with the result of another study of 82 PD patients, which found that younger patients and those with higher education performed better on the FAB test and that the severity of the disease was correlated with FAB performance [24] . Our study also found that patients with longer disease duration and more severe motor disabilities exhibited more severe frontal behavioral changes.…”
Section: Discussionsupporting
confidence: 87%
“…Risk factors responsible for cognitive impairment include advanced age, low educational level, long disease duration, severity of motor signs, rigid-akinetic PD variant, depression and psychosis [38]. Patients with low educational level are particularly susceptible to the deleterious effect of depression on cognition [42]. The prevalence of dementia in PD is about 31% [38].…”
Section: Depression and Cognitive Impairment In Pdmentioning
confidence: 99%
“…Cognitive impairment secondary to a comorbid neuropsychiatric disorder, such as depression and Alzheimer's disease, may superimpose to those typically seen in PD dementia, turning difficult the diagnostic process. It is worth mentioning that patients with low educational level are particularly susceptible to the deleterious effect of depression on cognition 111 . Recently, the Movement Disorders Society operationalized the diagnosis of PD dementia.…”
Section: Cognitive Impairment and Dementiamentioning
confidence: 99%